Humanoid Robots in the Therapy of Children with Autism Spectrum Disorders: Opportunities and Risks - Kossewska, Joanna (Roczniki Kulturoznawcze, 2024)
Autism spectrum disorders (ASD) are due to many etiological factors and despite the constant interest of researchers they constitute an intriguing mystery. The incidence of these neurodevelopmental disorders has been steadily increasing in the general population over recent decades. Inter-individual differences are significant, so effective methods of educational and therapeutic interactions are still being sought. Great hopes are placed on contemporary social robotics, a rapidly developing field, which can provide many practical solutions. However, humanoid robots are also becoming an inspiring proposition in the field of therapy and education of children with autism, but its effectiveness is still the subject of many experimental studies. The aim of the article is to critically reflect on the ethical aspects of using robots to help people with autism. The presentation of research results on the use of humanoid robots in the diagnosis and therapy of people with autism underpins reflections grounded in the fundamental axiological values and rights of people with autism be protected against abuse.